(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the challenges English language instructors face in designing fair and valid assessments for English Language Learners (ELLs) at Abu Issa College. Using a descriptive survey approach, data were collected from instructors through a questionnaire consisting of Likert-scale and open-ended items. Findings indicate that major challenges include insufficient training in assessment, time constraints, large class sizes, mixed student proficiency levels, and limited institutional support. Instructors also highlighted the importance of professional development, collaboration, and access to updated assessment resources in enhancing test validity and fairness. The study underscores the significant impact of assessment quality on students’ motivation and learning outcomes. Practical recommendations are provided to support instructors in developing more effective and equitable assessments in EFL contexts.